2011
DOI: 10.1108/02683941111124836
|View full text |Cite
|
Sign up to set email alerts
|

Fairness perceptions and satisfaction with components of pay satisfaction

Abstract: Purpose -The purpose of this paper is to integrate two streams of research and investigate the associations of different forms of justice perceptions on attitudinal reactions to four components of compensation: pay level, pay raises, benefits, and structure and administration In doing so, it responds to calls for more primary studies linking interactional justice perceptions to pay satisfaction. Design/methodology/approach -In total, 151 technology professionals employed at an international consulting company … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 55 publications
(135 reference statements)
2
61
1
1
Order By: Relevance
“…People are not concerned if those in other jobs make more money, but they are concerned if people in the same job earn more. Pay satisfaction is affected by how an individual's salary compares to the others in the same rather than people in general jobs, according to the equity theory of motivation (Jawahar & Stone 2011;Judge et al 2010;Spector 1997;Williams, McDaniel & Ford 2007;Williams et al 2008). Rice et al (1990) found a significant practically large correlation (0.50) between pay and job satisfaction in a sample of mental health professionals who all had the same jobs.…”
Section: Financial Well-beingmentioning
confidence: 99%
“…People are not concerned if those in other jobs make more money, but they are concerned if people in the same job earn more. Pay satisfaction is affected by how an individual's salary compares to the others in the same rather than people in general jobs, according to the equity theory of motivation (Jawahar & Stone 2011;Judge et al 2010;Spector 1997;Williams, McDaniel & Ford 2007;Williams et al 2008). Rice et al (1990) found a significant practically large correlation (0.50) between pay and job satisfaction in a sample of mental health professionals who all had the same jobs.…”
Section: Financial Well-beingmentioning
confidence: 99%
“…Pay has potentially important behavioural effects because much effort and performance is exercised voluntarily (Colling and Terry, 2010), and perceptions of "decent" levels and processes of pay combine with job content, conditions and hours to shape employee commitment and work motivation (Stevenson and Wolfers, 2013). Pay is thus not simply a function of the external labour market but reflects the need of employers to recognise employee concerns in order to motivate discretionary effort (De Saá-Pérez and García-Falcón, 2002;Jawahar and Stone, 2011).…”
Section: Dimensions Of a Lwmentioning
confidence: 99%
“…Informational justice primarily alters reactions to procedures because explanations provide the information needed to evaluate structural aspects of the process. Consistent with Greenberg's () proposal, Colquitt () identified distributive justice, procedural justice, interpersonal justice, and informational justice as the four factors comprising the construct of organizational justice (see also Ambrose, ; Bies, ; Judge & Colquitt, ; Jawahar, ; Jawahar & Stone, ; Thurston & McNall, ).…”
Section: Justice Perceptionsmentioning
confidence: 81%